Pengaruh Variasi Konsentrasi Ekstrak Daun Kelor (Moringa oleifera Lamk) Terhadap Efek Antiinflamasi Sediaan Emulgel - Octavianus Robby; Fransisca Gloria; Tunik Saptawati (FORIKES, 2022)
Moringa is a plant that is often used as a treatment and contains phytochemical compounds, one of which is a flavonoid that can be used as an anti-inflammatory. The purpose of this study was to formulate the ethanolic extract of Moringa leaves in the form of an emulgel with various extract concentrations of 5%, 7.5%, 10%. Emulgel formula consists of ethanol extract of Moringa leaves, carbopol 940, TEA, tween 80, methyl paraben, propyl paraben, propylene glycol and aquadest. Examination of the physical characteristics of the emulgel included: organoleptic, homogeneity, pH, spreadability, adhesion. The emulgel preparation was tested for its anti-inflammatory effect on male white rats of the wistar strain induced by carrageenan. The data obtained were analyzed statistically, namely the Anova test. The results of the examination of the characteristics of the emulgel which included organoleptic, homogeneity, pH, dispersion, and adhesion met the requirements for topical preparations. In the anti-inflammatory effect test of formula III, the highest percentage of inflammation reduction was 14.40% compared to the negative control, formula I and formula II. The Aova test results showed a p value <0.05. It was concluded that there were significant differences in the effect of variations in the concentration of Moringa leaf extract.Keywords: emulgel; Moringa leaf extract; anti-inflammatory ABSTRAK Kelor merupakan tanaman yang sering dimanfaatkan sebagai pengobatan dan mengandung senyawa fitokimia yang salah satunya adalah flavonoid yang dapat digunakan sebagai antiinflamasi. Tujuan penelitian ini adalah memformulasikan ekstrak etanol daun kelor dalam bentuk sediaan emulgel dengan variasi konsentrasi ekstrak 5%, 7,5%, 10%. Formula emulgel terdiri dari ekstrak etanol daun kelor, carbopol 940, TEA, tween 80, metil paraben, propil paraben, propilenglikol dan aquadest. Pemeriksaan karakteristik fisik emulgel meliputi: organoleptis, homogenitas, pH, daya sebar, daya lekat. Sediaan emulgel diuji efek antiinflamasi pada tikus putih jantan galur wistar yang diinduksi karagenan. Data yang diperoleh dianalisis secara statistik yaitu uji Anova. Hasil pemeriksaan karakteristik emulgel yang meliputi organoleptis, homogenitas, pH, daya sebar, daya lekat memenuhi syarat sediaan topikal. Pada uji efek antiinflamasi formula III, nilai persen penurunan radang yang paling tinggi yaitu 14,40% dibandingkan kontrol negatif, formula I dan formula II. Hasil uji Aova menunjukkan nilai p <0,05. Disimpulkan bahwa terdapat perbedaan efek secara signifikan dari variasi konsentrasi ekstrak daun kelor.Kata kunci: emulgel; ekstrak daun kelor; antiinflamasi